Assessing survival of wild-caught snakes in open venom production systems. (November 2017) - Sasa, Mahmood; Arias Ortega, Jazmín; Bonilla-Murillo, Fabián
Abstract: We evaluate adaptation of eleven species of wild-caught snakes maintained in captivity for venom production using two procedures for estimating survival rates. Kaplan-Meier estimations of survival time provide a better account of subsistence in captivity than estimations based solely on mean time to death. Highland and mid-elevation species are better adapted to our captive settings, but factors such as body condition at admission, locality of origin, seasonality, and maintenance protocol, affect the studied species differently. Periodic estimations of the collection's mortality rates, coupled with necropsy analyses, are recommended to assess adaptation and to develop acceptable species-specific management practices in captivity. Highlights: Proper maintenance protocols in snake captive systems require the assessment of survival time. Kaplan-Meier estimations better accounted for survival than estimations based on mean time to death. Mountain species show better survival times than lowland species in the study system. Other factors also affect survival in captivity, but the effects are species-specific.